Correlation of BIPQ score with socioeconomic characteristics of patients with COVID-19 pneumonia and CT severity score - Jankovic, Jelena; Sljivic, Aleksandra; Djukic, Vladimir; Vukomanovic, Vladan; Kapor, Suncica; Blagojevic, Nikola; Blagojevic, Dragana; Guslarevic, Isidora; Savic, Predrag; Nesic, Ivan; Karic, Uros; Stjepanovic, Mirjana (The Journal of Infection in Developing Countries, 2025)
Introduction: Coronavirus disease 2019 (COVID-19) rapidly became a global pandemic with clinical manifestations ranging from asymptomatic infection to life-threatening illness. While physician assessment of disease severity is largely objective, patient perception of illness is often influenced by psychosocial and demographic factors. This study aimed to explore determinants of illness perception among patients hospitalized with COVID-19. Methodology: A cohort of 262 patients with confirmed SARS-CoV-2 infection was evaluated. Baseline characteristics included age, gender, smoking history, body mass index, and sociodemographic information (relationship status, education, employment, and physical activity). Disease severity was assessed using chest computed tomography (CT) scans. Illness perception was measured with the Brief Illness Perception Questionnaire (BIPQ). Results: The median patient age was 56.3 years, and 65.6% were male. More than half (56.5%) had completed higher education, 90% were married or in a relationship, 57.6% were unemployed, and 85.9% reported no regular physical activity. Male patients demonstrated higher absolute CT scores (p = 0.018) but lower BIPQ scores. Severe pneumonia, as defined by CT findings, correlated with longer hospitalization, although no significant differences in total BIPQ scores were observed across CT severity groups. Illness perception was not influenced by education (p = 0.43), employment (p = 0.096), or physical activity (p = 0.94). However, relationship status significantly affected total BIPQ scores (p = 0.034). Conclusions: The study found BIPQ useful for rapid illness perception assessment, recommended for routine practice. Socio-economic factors influenced responses, while CT severity did not. Linking CT scores with BIPQ may identify patients at risk of psychological distress.